2022
DOI: 10.3390/ijms23052521
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Kidney Disease with Extracellular Vesicles from Mesenchymal Stem Cells and CD133+ Expanded Cells: A Comparative Preclinical Analysis

Abstract: Chronic kidney disease (CKD) is characterized by structural abnormalities and the progressive loss of kidney function. Extracellular vesicles (EVs) from human umbilical cord tissue (hUCT)-derived mesenchymal stem cells (MSCs) and expanded human umbilical cord blood (hUCB)-derived CD133+ cells (eCD133+) maintain the characteristics of the parent cells, providing a new form of cell-free treatment. We evaluated the effects of EVs from hUCT-derived MSCs and hUCB-derived CD133+ cells on rats with CDK induced by an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…Different EVs have been used to treat different diseases [ 84 , 85 , 86 , 87 ]; however, to date, there is no definition of which EV source is the best and for which disease or injury. Our group has previously shown the potential of E-CD133 EVs in the treatment of cardiac injury, in a rat model of myocardial infarction [ 88 ], and in the recovery of renal function, in a rat model of chronic kidney disease [ 26 ]. Future experiments will be able to further assess the relationship between miRNAs (and proteins) identified in E-CD133 EVs, their targets and modulated pathways, and the effects already described.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Different EVs have been used to treat different diseases [ 84 , 85 , 86 , 87 ]; however, to date, there is no definition of which EV source is the best and for which disease or injury. Our group has previously shown the potential of E-CD133 EVs in the treatment of cardiac injury, in a rat model of myocardial infarction [ 88 ], and in the recovery of renal function, in a rat model of chronic kidney disease [ 26 ]. Future experiments will be able to further assess the relationship between miRNAs (and proteins) identified in E-CD133 EVs, their targets and modulated pathways, and the effects already described.…”
Section: Resultsmentioning
confidence: 99%
“…E-CD133 is a promising cell population little explored in the literature so far. We recently demonstrated the potential of E-CD133 and their EVs in the treatment of cardiac and renal lesions [ 21 , 26 ]. Here, we extended the characterization of E-CD133 EVs by analyzing their miRNA cargo.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As summarized in Additional file 2 : Table S2, the EVs from ADSCs and BMSCs exhibited similar characteristics and exerted protective functions in a wide array of diseases like EPC-EVs. Recently, Miyasaki and colleagues compared the efficiency of EVs from mesenchymal stem cells and EPCs in treating chronic kidney disease and found similar improvement in renal function in terms of serum albumin, cystatin C, crystals in the renal tubules, and fibrosis, rather than staining of alpha-smooth muscle actin [ 176 ]. However, the direct comparison between different types of EVs was rare, and further studies are needed.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%
“…However, under pathological conditions, the NFs can stimulate inflammation, fibrosis, coagulation, and oncogenesis. Recently, both in vivo and in vitro studies have shown explosive advances regarding the protective role of NFs in various renal diseases [8,[15][16][17][18].…”
mentioning
confidence: 99%